PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS DENGAN MEDIASI KEPUASAN PASIEN RAWAT INAP PADA KELUARGA SEHAT HOSPITAL PATI - Puspitasari, Mei Gawati; Edris, Mochamad (Jurnal Analisis Manajemen, 2011)
The purpose of this study is to analysis the effect of service quality variable toward patient loyalty mediated by patients satisfaction in Keluarga Sehat Hospital Pati. This study used samples of 100 respondent. Methods of collecting data through questionnaires using a Likert scale with a purposive sampling method. Data analysis methods used are quantitative analysis using path analysis techniques (path analysis). The result showed : 1) Service Quality variable had a significant effect on patient loyality but not directly 2) Service quality variable had a significant efeect on patient loyality. 3) Service quality variable had a significant effect on loyality through the mediating variable of customer loyalty. 4) Service Quality had a significant effect on customer loyalty through customer satisfaction. This result showed that service quality can establish customer satisfaction, patients will feel happy to get additional service than what their expect so they will be satisfied and will form a customer loyalty in Keluarga Sehat Hospital Pati.